The Presence of Chewing Lice (Insecta: Phthiraptera) Species on Wild Grey Partridge (Perdix perdix canescens) - Aksin, Nursel; Oncel, Taraneh (Medwell Online, 2011)
This research was conducted to determine species of chewing lice (Phithiraptera) on wild grey partridge (Perdix perdix canescens) (Galliformes: Phasianidae). For this purpose, 36 wild grey partridges, obtained in different areas of Elazig, Tunceli, Bingol, Erzurum provinces (the Eastern Anatolian region) of Turkey in 2006 and 2009, during the hunting season between October-January were examined in terms of ectoparasites. It was established that 21 (59.00%) wild grey partridges were infested with at least one chewing lice species. A total of four chewing lice were collected from the infested grey partridges and the diagnosis of them led to the discovery of four different species. Of the infested grey partridges, 8 (22%) were found to have Goniodes dispar, 6 (17%) were found to have Goniocotes microthorax, 5 (14%) were found to have Cuclotogaster heterogrammicus and 2 (6%) was found to have Amyrsidea perdicis. In this study, the evidence of G. dispar, G. microthorax, C. heterogrammicus and A. perdicis on wild grey partridges is reported for the first time in Turkey.
Keywords: Chewing lice; grey partridge; Perdix perdix canescens; hunting season; wild grey; Turkey